2019
DOI: 10.4149/bll_2019_135
|View full text |Cite
|
Sign up to set email alerts
|

Preventative effect of diclofenac sodium and/or diltiazem in rats with epidural fibrosis

Abstract: OBJECTIVE: Spinal epidural fi brosis is commonly seen after laminectomy. There is not yet proven any agent preventing fi brosis in clinical usage. We used diclofenac sodium and diltiazem, which are fi brosis inhibitors. METHODS AND MATERIALS: 40 rats were divided into four groups of equal numbers: control, diclofenac sodium, diltiazem, and diclofenac sodium + diltiazem. Laminectomies were performed at L5 and L6. After a 4 week period, the rats were decapitated and the vertebral column blocks were removed for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
2
0
2
Order By: Relevance
“…For the inhibition of specific inflammatory cytokines, etanercept, a TNF-α blocker, [1] tamoxifen, a TGF-β blocker, [7] methyl palmitate, [18] and dexmedetomidine [4] have been extensively investigated. Also, there are studies using diclofenac sodium [20] and curcumin [21] as anti-inflammatory agents. All these studies showed that both inflammatory cytokine inhibition and the use of anti-inflammatory agents significantly reduced the development of epidural fibrosis by producing anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the inhibition of specific inflammatory cytokines, etanercept, a TNF-α blocker, [1] tamoxifen, a TGF-β blocker, [7] methyl palmitate, [18] and dexmedetomidine [4] have been extensively investigated. Also, there are studies using diclofenac sodium [20] and curcumin [21] as anti-inflammatory agents. All these studies showed that both inflammatory cytokine inhibition and the use of anti-inflammatory agents significantly reduced the development of epidural fibrosis by producing anti-inflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the methods that create a mechanical barrier show different efficacy, they significantly reduce the development of epidural fibrosis. In addition, several studies are available in the literature reporting significantly reduced epidural fibrosis, using agents such as pentoxifylline [23] with an anti-fibroblastic effect, and diltiazem, [20] an fibroblast growth factor-2 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Les composés phénoliques, tels que les polyphénols, les terpénoïdes et les tanins interagissant avec les régions aliphatiques autour du résidu lysine des protéines et sont des antioxydants avec une activité anti-inflammatoire puissante [45,46]. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. De plus, il a été démontré que Rosa musquée et Rosa canina L. réduisaient la production de plusieurs cytokines pro-inflammatoires et de chimiokines [49,50].…”
Section: Fig2 Corrélation Entre La Concentration Et L'inhibition (%)unclassified
“…[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. De plus, il a été démontré que Rosa musquée et Rosa canina L. réduisaient la production de plusieurs cytokines pro-inflammatoires et de chimiokines [49,50]. Il est également intéressant de noter que l'extrait de R.canina empêche la dénaturation de la SAB et de l'albumine d'oeuf, a une activité antioxydante in vitro qui est également une caractéristique de certains anti-inflammatoires [51,52].…”
Section: Fig2 Corrélation Entre La Concentration Et L'inhibition (%)unclassified